Clinical characteristics of pulmonary embolism at extremely high altitude: a single-center retrospective study - Wu, Jialin; Zhang, Jianli; Wang, Rui; Han, Xiaobo; Wang, Wan; Chen, Qingqing; Gao, Yali; Wusifujiang, Munire; Jiang, Peng (Frontiers in Public Health, 2025)
BackgroundExposure to high altitude (HA) has been shown to significantly increase the risk of venous thromboembolism (VTE). However, the clinical characteristics of VTE at extremely high altitudes remain poorly understood. In this single-center retrospective study, we aimed to compare the clinical characteristics and prognoses of pulmonary embolism (PE) patients at extremely high altitudes with those at low altitudes (LA).MethodsThis retrospective analysis focused on PE patients treated at the General Hospital of Xinjiang Military Command between November 1, 2019, and November 1, 2022. The high-altitude group (HA-Group) consisted of patients who sought medical treatment after they had fallen ill into the plateau area, and the low-altitude group (LA-Group) consisted of local residents.ResultsWe identified a total of 17 PE patients in the HA-Group and 62 patients in the LA-Group. The average altitude in the HA-Group was 5,041 ± 85.34 m, and 802.1 ± 11.10 m in the LA-Group (p < 0.0001). Hematological indicators, including red blood cells, lymphocytes, platelet counts, hemoglobin, PT, APTT, the INR and uric acid, were significantly higher in the HA-Group than in the LA-Group. Kaplan–Meier curve analysis demonstrated that the time to complete resolution of pulmonary thrombosis was significantly shorter in the HA-Group than in the LA-Group (log-rank p = 0.033).ConclusionThis retrospective study revealed the clinical characteristics of PE patients at extremely high altitudes. High-altitude exposure may increase the susceptibility of young people to PE, and abnormal serum uric acid metabolism may be a potential risk factor for PE in high altitude areas.